2016
DOI: 10.22359/cswhi_7_2_13
|View full text |Cite
|
Sign up to set email alerts
|

Stress factors in the work of nurses

Abstract: Abstract:Being a nurse is amongst one of the toughest professions. It is a profession in which the nurse will be in contact with different kinds of stress factors. There are often encounters with death, suffering, as well as dying and terminally ill patients. Nurses must be able to communicate with patients who react differently to illness and hospitalization and those patients who can even cause conflicts. In addition to the direct workloads regarding this range of problems there are also bad relationships in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
(1 reference statement)
0
1
0
Order By: Relevance
“…Nurses who work in Psychiatric hospitals according to the study of Abdullah and Abbas (2015) found male and female nurses would experience work stress. A study explained that nurses working in Psychiatric hospitals experience moderate levels of work stress (Hasan, 2017), and inpatient rooms for mental patients are the rooms that have the highest level of work stress on nurses compared to other rooms (Konzon & Zacharova, 2016;Totman, Hundt, Wearn, Paul, & Johnson, 2011). Another study conducted in the inpatient unit of the Regional Psychiatric hospital of North Sumatra Province explained that nurses working in inpatient units experienced work stress (Ulfah, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses who work in Psychiatric hospitals according to the study of Abdullah and Abbas (2015) found male and female nurses would experience work stress. A study explained that nurses working in Psychiatric hospitals experience moderate levels of work stress (Hasan, 2017), and inpatient rooms for mental patients are the rooms that have the highest level of work stress on nurses compared to other rooms (Konzon & Zacharova, 2016;Totman, Hundt, Wearn, Paul, & Johnson, 2011). Another study conducted in the inpatient unit of the Regional Psychiatric hospital of North Sumatra Province explained that nurses working in inpatient units experienced work stress (Ulfah, 2011).…”
Section: Introductionmentioning
confidence: 99%